"Scorpion"-shaped mono(carboxy)porphyrin-(BODIPY)2, a novel triazine bridged triad: synthesis, characterization and dye sensitized solar cell (DSSC) applications1. Issue 22 (14th June 2015) - Galateia, Zervaki E.; Agapi, Nikiforou; Vasilis, Nikolaou; Sharma, Ganesh D.; Athanassios, Coutsolelos G.
<x xml:space="preserve">Abstract</x> A novel BODIPY-porphyrin triad is prepared with two BODIPY molecules covalently attached via a 1, 3, 5-triazine molecule to a free-base carboxyphenyl meso-substituted porphyrin.